Analyzing the Profile and Purchase Intentions of Green Consumers in Poland - Apaydin, Fahri; Szczepaniak, Magdalena (Ekonomika, 2017)
Consumers have started to search for green products and services as their environmental consciousness has been increasingly rising. As a result, companies have been forced to implement the strategies of green marketing, and marketers began to consider the differences existing between various segments of market in terms of green awareness. The aims of this study are to divide the market into specific consumer groups according to the environmental variables that have been viewed as important in the consumption process of the eco-friendly products; it is done so as to determine whether the significant differences between segments exist in terms of demographic variables and to discover a profile of green consumers in Poland. The self-administrated questionnaire sent via emails and networking websites served as a measurement instrument. As a result of the analyses, the environmental variables allowed for making a segmentation of consumers and discovering three groups: the Potential Greens, True Greens and Browns. Age and gender seem to be differentiating between greener segments and those consumer groups that are less environmentally conscious, while education and income are not statistically significant.
Keywords: Green Marketing; Polish consumers; green consumer segments; environmental consciousness